PsycEXTRA Dataset 2011
DOI: 10.1037/e602762012-001
|View full text |Cite
|
Sign up to set email alerts
|

Does Cash for School Influence Young Women's Behavior in the Longer Term? Evidence from Pakistan

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 6 publications
0
38
0
Order By: Relevance
“…These CCTs generally included household co-responsibilities in order to receive benefits, such as health clinic visits for children under five, school enrollment and primary-aged children and attendance at monthly health education meetings. Alam and colleagues (2010), used a quasi-experimental case-control design to demonstrate that the Pakistani Female School Stipend Program, also a CCT targeted towards girls in sixth to eighth grades, increased age at marriage by 1.2 to 1.5 years over a six-year period. The same program had no impact on the probability of ever giving birth and only a weakly significant effect on the total number of live births.…”
Section: Social Cash Transfers Fertility and Marriagementioning
confidence: 99%
“…These CCTs generally included household co-responsibilities in order to receive benefits, such as health clinic visits for children under five, school enrollment and primary-aged children and attendance at monthly health education meetings. Alam and colleagues (2010), used a quasi-experimental case-control design to demonstrate that the Pakistani Female School Stipend Program, also a CCT targeted towards girls in sixth to eighth grades, increased age at marriage by 1.2 to 1.5 years over a six-year period. The same program had no impact on the probability of ever giving birth and only a weakly significant effect on the total number of live births.…”
Section: Social Cash Transfers Fertility and Marriagementioning
confidence: 99%
“…(Each cohort received the same intervention.) The remaining four evaluations of interventions that reported at least marginally significant findings were evaluations of cash transfer programs (Alam, Baez, and Del Carpio 2010;Baird 2010) and of a health services intervention (Portner, Beegle, and Christiaensen 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Of the nine evaluations of interventions measuring impact on adolescent marriage, three revealed an unambiguously significant impact in the direction of reducing early marriage ( Erulkar and Muthengi 2009;Gulemetova-Swan 2009;Hallfors et al 2011). Four of the remaining six interventions in this category yielded results that were in the direction of such impact but were either marginally statistically significant or only some of the findings were statistically significant (Alam, Baez, and Del Carpio 2010;Baird et al 2010;Rahman and Daniel 2010;Duflo, Dupas, and Kremer 2011 [free uniform component]). Of the nine studies that evaluated contraceptive use, five found exclusively significant effects (Kim et al 2001;Lou et al 2004;Daniel, Masilamani, and Rahman 2008;Kanesathasan et al 2008;Erulkar and Muthengi 2009), two found mixed results (Eggleston et al 2000;Okonofua et al 2003), and two found…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations